THE EFFECT OF PERCEIVED VALUE, SERVICE QUALITY, AND BRAND IMAGE ON CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE AT PT FIRST MITRA MANDIRI - Hanisa Aulia Putri; Ramli; M. Gita Indrawan (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
Abstract-This study aims to analyze the effect of Perceived Value, Service Quality, and Brand Image on Customer Loyalty through Customer Satisfaction as an intervening variable among customers of PT First Mitra Mandiri, a company located in Batam City and engaged in spa. This research is motivated by the increasingly competitive spa industry and the importance of maintaining customer loyalty as a key factor for business sustainability. This study employed a quantitative approach using a survey method. The population consisted of all First Spa Batam customers who had used the spa services at least twice. The sampling technique used was accidental sampling, resulting in a sample of 125 respondents. Data were collected through questionnaires and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the assistance of SmartPLS software. The results indicate that Perceived Value, Service Quality, and Brand Image have a positive and significant effect on Customer Satisfaction. Furthermore, Perceived Value, Service Quality, Brand Image, and Customer Satisfaction have a positive and significant effect on Customer Loyalty. The mediation analysis demonstrates that Customer Satisfaction successfully mediates the relationship between Perceived Value, Service Quality, and Brand Image and Customer Loyalty. This study concludes that enhancing customers’ perceived value, service quality, and a positive brand image can increase customer satisfaction, which in turn strengthens customer loyalty at First Spa Batam. Therefore, the company should continuously improve service quality, provide value that meets customer expectations, and strengthen its brand image in order to maintain and enhance customer loyalty.